Non-market valuation of natural and environmental resources in Central America and the Caribbean - Steve Shultz (CEPAL Review, 1997)
An inventory and assessment was made of 15 non-market valuation studies in Central American and Caribbean countries. Most utilized the contingent valuation method to determine willingness to pay for drinking water or protected areas. The method used suffered from a reliance on open-ended bidding, information framing and contingent scenarios lacking detail, limited population samples, and possible cultural-strategic biases associated with surveying local residents. Problems observed with respect to the single travel cost method study reviewed were a reliance on poor quality census data rather than visitor survey data, and unrealistic assumptions regarding transportation cost estimates, single-destination visitors, and consumer surplus levels of international visitors.